2020
DOI: 10.3389/fnins.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the Gene Coding for PGC-1α in Peripheral Blood Leukocytes of Patients With Parkinson’s Disease

Abstract: Decreased expression of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) is implicated in the pathophysiology of Parkinson's disease (PD). However, our understanding of the mechanism regulating the PGC-1α expression is still limited. We sought to determine whether the epigenetic modification of PPARGC1A (the gene encoding PGC-1α) could account for its diminished expression. We performed a study of PPARGC1A risk-SNP genotypes, methylation level, and the expression in blood from 171 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A connection between PGC-1α methylation and mtDNA copy number is established, and a negative correlation is reported between PGC-1α promoter methylation and both PGC-1α transcription and mtDNA copy number in neurological (53) and metabolic disorders (31,33,70). Consistent with this, we report a negative correlation between PGC-1α promoter hypermethylation and both mtDNA copy number and deletions in our control group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A connection between PGC-1α methylation and mtDNA copy number is established, and a negative correlation is reported between PGC-1α promoter methylation and both PGC-1α transcription and mtDNA copy number in neurological (53) and metabolic disorders (31,33,70). Consistent with this, we report a negative correlation between PGC-1α promoter hypermethylation and both mtDNA copy number and deletions in our control group.…”
Section: Discussionmentioning
confidence: 95%
“…Our data show genes that regulate mitochondrial biogenesis, fission and fusion are DM in our cohort. While we were unable to measure gene expression because of the low integrity of RNA extracted from the tissue source (buccal swabs) used in our study, previous studies have shown that differential methylation alters the expression of these genes (20,42,43,53). We investigated whether mitochondrial DNA copy number, a marker of mitochondrial function (46), was altered in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, regarding the genes with aberrant methylation, PPARGC1A (the gene encoding PGC-1α) and HLA-DRB5 (involved in neuroinflammation and immune system) could be suitable PD biomarker candidates. Both have been reported as hypermethylated in independent studies and in different tissues: PPARGC1A in the SN and peripheral blood [ 172 , 173 ], and HLA-DRB5 in peripheral blood and frontal cortex [ 151 , 154 ] ( Figure 2 ). HLA-DRB5 is also hypermethylated in AD [ 174 ]; additional studies should determine the sensitivity and specificity of this potential biomarker for PD.…”
Section: Epigenetic Pattern As Lbd Biomarkermentioning
confidence: 99%
“…The selective knockout of different PGC-1α isoforms in mice may lead to a decrease of dopamine content in the striatum and to an associated loss of DA neurons [ 148 ]. Accordingly, in human PD tissues, the levels of PGC-1α and of mitochondrial markers are reduced compared to control patients and are negatively correlated with the severity of the disease [ 148 , 153 , 154 , 155 , 156 , 157 ]. Conversely, primary fibroblasts from PD patients display upregulation of PGC-1α, even if its target genes involved in mitochondrial biogenesis and fatty acid β-oxidation processes are unchanged or downregulated and mitochondria display significant morphometric changes [ 158 , 159 ].…”
Section: Pgc-1s In Parkinson’s Diseasementioning
confidence: 99%
“…The low expression of PGC-1α observed in the PD brain is probably due to the high level of gene methylation that has been found in PD patients [ 155 ]. Dense DNA methylation is usually associated with gene repression, and the PGC-1α promoter is proximal to a non-canonical cytosine methylation site that is epigenetically modified in the brain of sporadic PD patients [ 153 ].…”
Section: Pgc-1s In Parkinson’s Diseasementioning
confidence: 99%